(untitled) (European Journal of Pure and Applied Mathematics, 2026)
Choosing the right options for sustainable traditional medicine development is a major challenge for healthcare policymakers and practitioners, especially with uncertainties introduced by political shifts and policy changes. A new approach is developed in this study to address this complex issue. Applying the alternative ranking using two-step logarithmic normalization (ARLON) based on picture fuzzy sets (PFS), this framework is the first of its kind in the literature. It helps identify the most appropriate strategies from options for sustainable traditional medicine development. The study combines the picture fuzzy ARLON approach with the FullEX technique to weigh criteria representing challenges to sustainable traditional medicine development. Sensitivity analysis scenarios and comparative analyses are conducted to test the approach’s robustness. Results show that "promotion of the validation of the safety, efficacy, and quality of medicinal plants and their products" and "concerted campaigns emphasizing the advantageous aspects of traditional medicine" are the most appropriate alternatives for sustainable traditional medicine development.